Netrin-1 controls inflammation in response to ischemic stroke through altering microglia phenotype - Yang, Xiaosheng; Liu, Yang; Zhong, Weijie; Li, Yi; Zhang, Wenchuan (Frontiers in Immunology, 2023)
Introduction: The current approaches that are used to treat ischemic stroke suffer from poor targeting, lack of effectiveness, and potential off-target effects, necessitating the development of new therapeutic strategies to enhance neuronal cell survival and regeneration. This study aimed to investigate the role of microglial Netrin-1 in ischemic stroke, a topic that has not been fully understood. Methods: Netrin-1 levels and its primary receptor expressions were investigated in cerebral microglia from acute ischemic stroke patients and age-matched control subjects. A public database (GEO148350), which supplied RNAseq results for rat cerebral microglia in a middle cerebral artery occlusion (MCAO) model, was analyzed to assess the expression of Netrin-1, its major receptors, and genes related to macrophage function. A microglia-specific gene targeting approach and a delivery system allowing for crossing the blood-brain barrier were applied in a mouse model for ischemic stroke to investigate the role of microglial Netrin-1. Netrin-1 receptor signaling in microglia was observed and the effects on microglial phenotype, apoptosis, and migration were analyzed. Results: Across human patients, rat and mouse models, activation of Netrin-1 receptor signaling was mainly conducted via its receptor UNC5a in microglia, which resulted in a shift in microglial phenotype towards an anti-inflammatory or M2-like state, leading to a reduction in apoptosis and migration of microglia. Netrin-1-induced phenotypic change in microglia exerted protective effects on neuronal cells in vivo during ischemic stroke. Conclusion: Our study highlights the potential of targeting Netrin-1 and its receptors as a promising therapeutic strategy for promoting post-ischemic survival and functional recovery.